A human rights framework towards the protection of minority languages and linguistic minorities in Africa : case studies of South Africa and Zimbabwe - Hansungule, Michelo (University of Pretoria, 2017)
This thesis examines and defends the use of a human rights framework for the protection of minority languages and linguistic minorities in Africa as an effective means to eliminate discrimination against linguistic minorities, protect minority languages, preserve linguistic minority identity and foster substantive equality between linguistic majorities and linguistic minorities. The argument that runs throughout the thesis is that in order to effectively integrate linguistic minorities, while allowing them to preserve their linguistic identity, the human rights framework should have two pillars with two clusters of rights. The first pillar consists of individual human rights of special relevance to linguistic minorities that ensure that linguistic minorities are placed on a substantially equal footing with other nationals of the state. Key rights are the rights to equality and non-discrimination on the basis of language. Other individual rights include freedom of expression, the right to culture, the right to participation, the right to a name, the right to family, the right to fair trial and the right to education. The second pillar consists of minorityspecific standards (rights and measures) designed to protect and promote the separate identity of minority language groups. These include prevention of assimilation, the right to identity and the right to use a minority language in the public and private spheres. This study argues that even though the international, regional and national human rights standards are general and often qualified and have some gaps and deficiencies, they provide a human rights framework for the protection of minority languages and linguistic minorities in Africa. The study recommends two approaches to assist in clarifying the normative content of minority language rights in Africa. On the one hand, there is the progressive interpretation approach, which does not introduce new standards for the protection of minority languages and linguistic minorities in Africa but allows the African Commission on Human and Peoples' Rights and African Court on Human and Peoples Rights to use articles 60 and 61 of the ACHPR to draw inspiration from the UN, European, Inter-American and national human rights systems to imply or infer minority language rights from the rights to equality and non-discrimination on the basis of language, right to identity, freedom of expression, right to culture, right to work, right to education, right to the protection of the family, the right of every child to a name and the right to a fair trial in the African Charter on Human and Peoples' Rights. On the other hand, there is the standard setting approach which entails the drafting of a specific treaty setting new standards for the protection of minority languages and linguistic minorities. To this end, the thesis suggests and provides a draft framing for a Protocol to the African Charter on Human and Peoples' Rights on Minority Language Rights in Africa.